INNOVATIVE STRATEGIES FOR INTEGRATING PROGRAMMING SKILLS IN INFORMATICS ENGINEERING DEPARTMENT - NAMRUDDIN, RESPATY; Syahrul, Syahrul; Lu'mu (Jurnal Vokasi Keteknikan, 2024)
This study aims to design and develop a Programming Skills Integration Model in the Informatics Engineering Department using the Project-Based Learning (PjBL) approach. The research method used is Research and Development (R&D) with the 4D development model: Define, Design, Develop, and Disseminate. The first step involved a needs analysis to identify the challenges and needs of students' programming skills. Next, a model design was conducted that included aspects of materials, learning methods, media, and evaluation. The model prototype was tested using expert validation and field trials to evaluate its effectiveness. The results showed that the model was validated by experts and effectively applied in improving students' programming skills. The high level ofpracticality and positive responses from students confirmed the potential use of the PjBL-based Programming Skills Integration Model in the context of informatics engineering education. Research recommendations include industry involvement in PjBL as well as further development to accommodate technological developments and industry needs.